Overall Survival for Stage III Breast Cancer Patients at DR. Mohammad Hoesin General Hospital Palembang and the Influencing Factors - Raehan Satya Deanasa; Mulawan Umar; Agita Diora Fitri (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: There is still a limited number of studies related to overall survival in breast cancer patients in Indonesia. This study determines the overall survival and the factor which can affect the survival of stage III breast cancer patients.Methods: This study was a retrospective study. Patients first diagnosed with stage III breast cancer from January 1 to August 31, 2018, at DR. Mohammad Hoesin General Hospital Palembang had been studied. The primary outcome of this study was overall survival. The sociodemographic, clinicopathology, and treatment factors were analyzed to identify the independent variables associated with overall survival using Kaplan-Meier and Cox proportional hazard regression.Results: In this study, 78 samples were included. The 3-year overall survival for stage III breast cancer was 71%. In the bivariate analysis, several factors including older age (> 40) (HR = 2.795, 95% CI 1.223–6.387), higher stages for IIIB (HR = 7.155, 95% CI 0.960–53.334), and IIIC (HR = (HR = 33.450, 95% CI 3.013-371.354), history of not undergoing surgical intervention (HR = 3.999, 95% CI 1.684–9.495), and adjuvant chemotherapy (HR = 2.768, 95% CI 1.211–6.327) have been associated significantly to lower overall survival. Multivariate analysis showed IIIC breast cancer stage as an independent factor and had a significantly increased probability of mortality (HR = 14.677, 95% CI 1.268–169.948).Conclusions: The stage at diagnosis was the only significant predictor for the survival outcome, indicating that early diagnosis may need more attention.